Strategy of innovative entrepreneurship: reasons of fixing as priority and concrete manifestations in modern conditions - A. S. Genkin (Путеводитель предпринимателя)
There is no universal way how to grow up the entrepreneur-innovator, however the article fixes the main features of this social type. Elements of innovative strategy of entrepreneurship are considered. The branch of payment and settlement services is investigated: it is remarkable for extraordinary high number and intensity of innovations. It is proved that introduction of payment innovations levels negative impact of a system economic crisis, and three business niches for innovative entrepreneurship in branch are designated.